Construction and standardization of an achievement test of social studies for 8th grade students. - Dr Rohtash (Innovative Research Thoughts, 2017)
The Present study was undertaken as an effort to construct and standardize an achievement test in Social Studies for the students of Class 8th. For this purpose, the content of textbook prescribed by H.S.E.B. for class 8th was taken up. Multiple choices questions were constructed by giving equal weightage to all the chapters and expert opinions were taken. Try out was conducted on a sample of 200 H.B.S.E. students of class 8th. Item analysis was done. After revising and discarding the poor items on the basis of index of difficulty value (P) and discriminating index (D.I.), final draft was prepared. Reliability and Validity of the achievement test was also calculated.